Glyphosate (Roundup): Fate in Aquatic Environment, Adverse Effect and Toxicity Assessment in Aquatic organisms - Thanomsit, Chutima; Saowakoon, Samnao; Wattanakornsiri, Amnuay; Nanuam, Jakkaphun; Prasatkaew, Witchuda; Nanthanawat, Phochit; Mongkolvai, Patcharee; Chalorcharoenying, Wanpen (Naresuan University Journal: Science and Technology (NUJST); Vol 28 No 1 (2020): January - March 2020, 2020)
Glyphosate (C 3 H 8 NO 5 P) is an organic substance in phosphonomethyl glycine group consisting of phosphorus in its structure. Its well-known trading name is Roundup, which is globally applied as herbicide. In Thailand, it has been widely applied, which results in it occupy in the top order of imported ago-chemical even though it was banned in many countries. Glyphosate application can cause contamination in groundwater and nearby surface water. Recently, there have been studies indicating that glyphosate contamination causes adverse effects on aquatic organism and is bio-accumulated and bio-magnified through food chain and finally reaches to human beings as top consumer. Glyphosate causes alterations in behavior, physiology, DNA, chromosome and bio-chemistry and moreover mortality in the case of exposure in high level. In this case, it may effect on aquatic population which is an important fishery stock in the future. In Thailand, there are lacks of fundamental data and knowledge thus it requires more studies or tests to fulfill this gap. As the importance mentioned above, the effect of glyphosate should be studied for developing the protection and management plan to reduce glyphosate contamination in aquatic organisms and environments.  Keywords: acetycholinesterase, aquatic organism, glyphosate, herbicide, roundup